Antidepressant Action of Optogenetic Stimulation of Serotonin-Prefrontal Cortical Projections in Chronically Stressed Female Mice via Hippocampal Modulation - Fuentes Alvarenga, Alberto Francisco (Université d'Ottawa / University of Ottawa, 2024)
Major depressive disorder is twice as prevalent in females. Selective Serotonin Reuptake Inhibitors are the first line of treatment; however, only 30% of patients remit with a 6-8-week latency. We used Unpredictable Chronic Mild Stress model of depression in female mice and optogenetically targeted serotonin projections at medial prefrontal cortex (mPFC) to assess new treatment options. Using transgenic Cre-mediated expression of light-sensitive channelrhodopsin-2 in serotonin neurons, mice were bilaterally stimulated in the mPFC during behavioural testing. UCMS induced anxiety/depression-like phenotypes with reductions of TPH+/FosB+ cells and reduction of serotonin axons, varicosities, and synaptic contacts. Opto-stimulation reversed behavioral effects in tail suspension and increased the chronic activation of serotonin neurons and CA1 pyramidal cells. UCMS induced depression/anxiety-like phenotypes in female mice that can be partly reversed by bilateral opto-stimulation of 5-HT projections to the mPFC, activating serotonin neurons and inducing hippocampal activity, resulting in activation of a mini-circuitry connecting mPFC-hippocampus-DR.
Keywords: Serotonin; Major Depressive Disorder; Optogenetics